2018
DOI: 10.1007/s11356-018-2123-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nine pharmaceutical active compounds in surface waters from Paraopeba River Basin in Brazil by LTPE-HPLC-ESI-MS/MS

Abstract: A simple, inexpensive, versatile, and environment-friendly extraction method, using low-temperature partitioning extraction (LTPE), was validated to quantify pharmaceutical-active compounds (PhACs) in surface water samples by high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS). The PhACs analyzed were acetaminophen, bezafibrate, diclofenac, diltiazem, fluconazole, linezolid, miconazole, ondansetron hydrochloride, and trimethoprim. The detection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…For example, some changes were observed during the separation between propranolol enantiomers when HSA concentration increases. 30 So, preliminary assays were performed at different voltages (ranging from 12 to 20 kV), temperatures (15-21 C), HSAs (10-20 μM), NDs (0%-0.25%, w/v), and pH values (8)(9)(10)(11). Related to the pH, the better results were obtained at pH 9.5.…”
Section: Optimization Of Ekc Experimental Conditions For the Chiral S...mentioning
confidence: 99%
“…For example, some changes were observed during the separation between propranolol enantiomers when HSA concentration increases. 30 So, preliminary assays were performed at different voltages (ranging from 12 to 20 kV), temperatures (15-21 C), HSAs (10-20 μM), NDs (0%-0.25%, w/v), and pH values (8)(9)(10)(11). Related to the pH, the better results were obtained at pH 9.5.…”
Section: Optimization Of Ekc Experimental Conditions For the Chiral S...mentioning
confidence: 99%
“…The second aspect concerns the matrix, since most of the studies were directed at the determination of LNZ in biological fluids or pharmaceutical preparations. Only recently did de Barros and coworkers [ 74 ] report a method for the simultaneous determination of LNZ among other drugs in the surface water of a Brazilian river, which is therefore useful for the determination in environmental field. To our knowledge, this paper is the only one reporting the determination of LNZ in natural waters.…”
Section: Perspectives Challenges and Conclusionmentioning
confidence: 99%
“…DCF has low biodegradability (Ahmed and Hameed 2018) and is considered a high-risk substance, included in the first Water Framework Directive list (Decision (EU) 2015/495, 2015, Directive 2013/39/EU 2013). Different concentrations of these drugs in water sources have already been reported in several countries, such as Brazil (Pereira et al 2016;de Barros et al 2018;Chaves et al 2020), Mexico (Rivera-Jaimes et al 2018, France (Andreozzi et al 2003), and Malaysia (Omar et al 2019). Usually, these concentrations are in the ng L −1 or μg L −1 scale (Chia et al 2021); however, they have already been found the values of 0.15 mg L −1 for SMX (Caldas et al 2018) and 0.19 mg L −1 for DCF (Campanha et al 2014).…”
Section: Introductionmentioning
confidence: 96%